A Petőfi-filológia legfőbb bázisa, a versgyűjtő füzetek - Szilágyi, Márton (Studia Litteraria, 2024)
The poem collecting notebooks had an important role from the beginning in the history of Petőfi editions – especially in terms of philology. This paper, however, does not focus on the philological importance of these manuscripts, but examines their function instead: why is it important that Petőfi created an autographical collection of texts for archival purposes? Petőfi started this method as early as the beginning of his career and the publishing agreements made it even clearer that his poems have market value not only as separate items, but also as a whole. Therefore, it was worth keeping the notebooks in order to establish the basics of a future collection.